Statistical Analysis of Habbatussauda’s Benefits for Health (Blood Pressure, Glucose and Uric Acid) - Sugiyanto Sugiyanto; Luqyana Khalda; Meksianis Zadrak Ndii (Biology, Medicine, & Natural Product Chemistry, 2019)
Habbatussauda is one of the traditional medicine existed since a long time ago and this is one of the drugs that recommended by the Prophet Muhammad. Habbatussauda’s benefits have been studied extensively in the healthcare. Habbatussauda has also been widely used to cure various diseases. This study revealed the benefits of Habbatussauda in lowering blood pressure, glucose and uric acid levels in 20 respondents that given Habbatussauda for 2 weeks. The blood pressure, glucose and uric acid levels were measured before and after consuming Habbatussauda. Blood pressure, glucose, and uric acid levels in the body will decrease after consuming Habbatussauda that shown in the statistical analysis of the obtained data.